Nurses' experience and attitudes towards inpatient aggression on psychiatric wards - Martina Tomagová; Ivana Bóriková; Martina Lepiešová; Juraj Čáp (University of Ostrava, 2016)
Aim: To determine the incidence rate of forms of inpatient aggression towards nurses who working on psychiatric wards; to identify their attitude to patient aggression, to the factors that condition the occurrence and management of aggression. To determine the differences between nurses in relation to educational training aimed at the issue of patient aggression. Design: Quantitative cross-sectional study. Methods: Selection of respondents was deliberate. The sample comprised 223 nurses with an average of 21.27 (± 11.41) years of clinical practice. Data collection was implemented by means of the self-assessment scales: Violence and Aggression of Patients Scale (VAPS), Attitude Towards Aggression Scale (ATAS), The Management of Aggression and Violence Attitude Scale-Likert (MAVAS-L). Results: 98.58% experienced inpatient aggression in the course of the previous year. Negative attitudes to patient aggression predominated in the sample. Nurses expressed strongest agreement with the idea that internal factors foster patient aggression. Regarding methods of aggression management, nurses expressed strongest agreement with the use of medical therapy and restraints. They held a neutral attitude towards the use of non-physical methods. The age of nurses had an effect on how strongly they agreed with the importance of internal factors in prompting patient aggression and with the use of medical therapy and restraints. Conclusion: A high percentage of nurses have had personal experience of various forms of patient aggression. Negative attitudes to aggression predominated in our sample of nurses, emphasizing the influence of internal factors. The attitude of nurses towards patient aggression influences the selection of aggression management strategies.